Retirement fund, social security and family support: Their roles in personal financial planning - Lim, Chee Chee (2015)
On 8 February 2013, Mr Ooi was looking out of the window in a small office room in a community hall, thinking long and hard on how he could devise a viable financial plan for En Ahmad in order to alleviate his strained financial situations. Mr Ooi was a licensed financial advisor.He had been voluntarily providing his service at the community hall in Jitra under a community movement initiated with the aim at helping people live a financially condifent life as the people there lack financial literacy and the financial world was too complex for them to shoulder without the help from professional financial advisors. On that day Mr Ooi had met En Ahmad, accompanied by his elder brother En Amran, for the third time. After the meeting, he had a comprehensive picture of En Ahmad’s predicament after En Ahmad, with the assistance of his elder brother En Amran, had truthfully disclosed his financial situations. By now Mr Ooi could work out a financial plan for En Ahmad darwing upon the funds available from three sources, namely the savings with retirement fund management organization, the financial aids provided by social security organization and family support, to lessen his financial burden.